Fuzzy Plastic Constitutive Model and Its Application to Subgrade. (24th September 2021) - Wang, Xigang; Jin, Liling; Xing, Yang; Fu, Mingfu
Abstract : The subgrade of a road is subjected to cyclic loading and unloading under the action of traffic loads. To study this mechanical response, the plastic membership function was introduced into the modified Cambridge model, and thus, the fuzzy plastic Cambridge constitutive model was obtained. With the continuous evolution of the plastic membership function from 0 to 1, the fuzzy plastic Cambridge constitutive model continuously transitions the plastic properties inside and outside the initial yield surface. The evolution of the plastic membership function can replace the complex hardening law. The reliability of the model was verified using triaxial tests and simple cyclic loading and unloading tests. Using the finite element method, the mechanical response of the subgrade under cyclic loading was calculated. The fuzzy plastic Cambridge model can explain the insignificant yield characteristics of geotechnical media. In the fuzzy plasticity theory, the stress inside and outside the initial yield surface can produce plasticity. Absolute plasticity was not observed; only different degrees of plasticity existed.